Environmental violence: a tool for planetary health research - Richard Marcantonio, PhD; Agustín Fuentes, ProfPhD (The Lancet Planetary Health, 2023)
Summary: From climate change to toxic pollution and the interactive effects of multiple pollution streams, human health is under siege. Human-produced environmental risks to health and wellbeing are high and contributing to patterns of global morbidity, mortality, economic inequality, displacement, and insecurity. The implications of human-produced environmental harms to global health are complex just as are their causes. The concept of environmental violence offers a potentially robust frame for engaging this issue. We argue that a more specified and structured framework and definition of environmental violence—focusing on human-produced harms by way of pollution emissions—is both timely and beneficial for engaging the complexities of global public health. To clarify why and how this is the case, we review the literature for publications that use the term environmental violence and we subsequently propose a specific definition focused on human-produced pollution along with a framework for tracking and analysing environmental violence and its constituent components. Finally, we discuss the potential value of our framework for research and policy making regarding human health.